Correlation of vitamin D levels with tear film stability and secretion in patients with dry eye syndrome. Issue 3 (22nd November 2016) - Jin, Ki Won; Ro, Jin Woo; Shin, Young Joo; Hyon, Joon Young; Wee, Won Ryang; Park, Shin Goo
Abstract: Purpose: To investigate tear film stability and secretion according to serum 25‐hydroxyvitamin D3 [25(OH)D] levels in dry eye patients. Methods: In this retrospective observational study, the medical charts of 92 patients who visited the Department of Ophthalmology at Hallym University Kangnam Sacred Heart Hospital from April to August 2015 were reviewed. Serum 25(OH)D levels were measured. Subjects were divided into three groups according to serum 25(OH)D levels: sufficient, inadequate or deficient group. Eye discomfort was measured by ocular surface disease index (OSDI). Tear break‐up time (TBUT), fluorescein staining score and Schirmer's tear secretion test were measured. Results: The mean age was 53.38 ± 13.69 years. Mean serum 25(OH)D level was 14.41 ± 5.98 ng/ml. Tear break‐up time (TBUT) and tear secretion were positively correlated with serum 25(OH)D levels ( r = 0.389, p = 0.001; and r = 0.428, p < 0.001, Pearson correlation test). Tear break‐up time (TBUT) and tear secretion were shorter in the vitamin D‐deficient group compared to the sufficient group (p = 0.022 and p = 0.004). Fluorescein staining scores and OSDI scores were not different between the three groups. Conclusion: Tear break‐up time (TBUT) and secretion were correlated with serum vitamin D levels. Vitamin D status may be an important factor for dry eye syndrome.